1996
DOI: 10.1037/1040-3590.8.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and convergent validity of the Aggression Questionnaire in an offender population.

Abstract: The study examined whether the 4-tactor structure of the Aggression Questionnaire (AQ: A. Buss £ M. Perry, 1992). consisting of Physical Aggression, Verbal Aggression. Hostility, and Anger, would replicate in an offender population. The AQ and Novaco's Anger Scale (NAS; R. Novaco, 1994) were administered to 200 adult offenders. The results of a confirmatory analysis suggested that the 4-factor model is a poor fit in an offender population. A 2-factor model was suggested: 1 factor combines Physical Aggression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
2
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 15 publications
11
93
2
8
Order By: Relevance
“…Previous research has shown that sex has effects only on PA and VA (Archer et al, 1995;Bernstein & Gesn, 1997;Ramirez, Andreu, & Fuhihara, 2001;Williams, Boyd, Cascardi, & Poythress, 1996) although the effects on VA are much slighter than on PA. Our results, then, seem to confirm that gender effects on AQ are mainly based on the PA scale, being men more physically aggressive than women, and that these effects are stable across samples.…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has shown that sex has effects only on PA and VA (Archer et al, 1995;Bernstein & Gesn, 1997;Ramirez, Andreu, & Fuhihara, 2001;Williams, Boyd, Cascardi, & Poythress, 1996) although the effects on VA are much slighter than on PA. Our results, then, seem to confirm that gender effects on AQ are mainly based on the PA scale, being men more physically aggressive than women, and that these effects are stable across samples.…”
Section: Discussionmentioning
confidence: 92%
“…This measure reliably differentiates between violent and nonviolent participants and correlates with responses to provoking scenarios, peer reports of aggression, and other self-reports of aggression [Harris, 1997;Morren and Meesters, 2002;O'Connor et al, 2001]. Although some research confirms the original factor structure of this measure [e.g., Harris, 1995], other results suggest that the original 29 items do not load sufficiently onto four factors, especially across different populations [Bryant and Smith, 2001;Vigil-Colet et al, 2005;Williams et al, 1996]. Bryant and Smith [2001] proposed a reduced version of the AQ that maintains the four original factors but includes only the three items with the highest loadings on each factor.…”
Section: Methodsmentioning
confidence: 89%
“…The Buss-Perry Aggression Questionnaire (BPAQ) is a well-known 29-item inventory with four subscales (i.e., Physical Aggression, Verbal Aggression, Anger, and Hostility). It is scored on a 5-point Likert scale and has been shown to have excellent psychometric properties [Buss and Perry, 1992;Tremblay and Ewart, 2005;Williams et al, 1996]. In this study, physical aggression, verbal aggression, trait anger, and hostility were indexed by participants' scores on the Physical Aggression (a 5 .84), Verbal Aggression (a 5 .71), Anger (a 5 .79), and Hostility (a 5 .80) subscales, respectively.…”
Section: Personality Inventoriesmentioning
confidence: 99%